Evidence of a double anaerobic threshold in healthy subjects. (23rd June 2021) - Rovai, Sara; Magini, Alessandra; Cittar, Marco; Masè, Marco; Carriere, Cosimo; Contini, Mauro; Vignati, Carlo; Sinagra, Gianfranco; Agostoni, Piergiuseppe
Abstract: Aims: The anaerobic threshold (AT) is an important cardiopulmonary exercise test (CPET) parameter both in healthy and in patients. It is normally determined with three approaches: V-slope method, ventilatory equivalent method, and end-tidal method. The finding of different AT values with these methods is only anecdotic. We defined the presence of a double threshold (DT) when a ΔVO2 > 15 mL/min was observed between the V-slope method (met AT) and the other two methods (vent AT). The aim was to identify whether there is a DT in healthy subjects. Methods and results: We retrospectively analysed 476 healthy subjects who performed CPET in our laboratory between 2009 and 2018. We identified 51 subjects with a DT (11% of cases). Cardiopulmonary exercise test data at rest and during the exercise were not different in subjects with DT compared to those without. Met AT always preceded vent AT. Compared to subjects without DT, those with DT showed at met AT lower carbon dioxide output (VCO2 ), end-tidal carbon dioxide tension (PetCO2 ) and respiratory exchange ratio (RER), and higher ventilatory equivalent for carbon dioxide (VE/VCO2 ). Compared to met AT, vent AT showed a higher oxygen uptake (VO2 ), VCO2, ventilation, respiratory rate, RER, work rate, and PetCO2 but a lower VE/VCO2 and end-tidal oxygen tension. Finally, subjects with DT showed a higher VO2 increase during the isocapnic buffering period. Conclusion: Double threshold was present in healthy subjects. The presence of DT does not influence peak exercise performance, but it is associated with a delayed before acidosis-induced hyperventilation.